A selective approach to parallelise Bees Swarm Optimisation metaheuristic: application to MAX-W-SAT. (23rd January 2008) - Sadeg, Souhila; Drias, Habiba
In this paper, we present a parallel version of the Bees Swarm Optimisation (BSO) metaheuristic. Firstly, we present a sequential algorithm, then we expose the original and innovative approach used for its parallelisation. Experiments comparing the performances of the sequential and the parallel algorithms in solving instances of the weighted maximum satisfiability problem are presented. A comparison is also done between BSO and other metaheuristics performances.